2016
DOI: 10.1007/s10549-016-3964-z
|View full text |Cite
|
Sign up to set email alerts
|

A collaborative approach to cancer risk assessment services using genetic counselor extenders in a multi-system community hospital

Abstract: This study demonstrates the feasibility of CGCs and GCEs collaborating to improve access to quality services in an efficient manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…Although genetics health professionals are currently the main targeted users of the BWA, further survey addressing BWA clinical use should strive to reach non-genetic clinicians such as breast surgeons, oncology specialists and general practitioners who will be increasingly involved in BC risk counselling [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although genetics health professionals are currently the main targeted users of the BWA, further survey addressing BWA clinical use should strive to reach non-genetic clinicians such as breast surgeons, oncology specialists and general practitioners who will be increasingly involved in BC risk counselling [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This international survey revealed that the BWA is mostly valued by health professionals’ using it. However, considering that further BOADICEA development plans to include additional factors, to facilitate uptake of the BWA in clinical practice, technological (e.g., step-wise assessment), organisational initiatives (e.g., involving patients or non-genetic professionals such as a nurse navigator [ 37 ]) and training initiatives should also be considered. We intend to repeat this survey when the new version of the BWA becomes available to monitor its acceptability.…”
Section: Discussionmentioning
confidence: 99%
“…Encouragingly, other recent work supports the strategy of moving the focus of TGC from consent to results disclosure and ensuring that consultation with genetics experts will be available and prioritized for more complicated cases. First, there is research in cancer genetics around “genetic counselor extenders” 15 with a team approach where a nurse ‘extender’ provided targeted discussions and pre-test consent in cases that are considered more straightforward risk assessments. Lieberman et al 16,17 presented qualitative data from a population screening program for BRCA1/2 in Israel that utilized written education materials for pre-test consent.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional model of direct patient referral with in‐person, one‐on‐one genetic counseling remains the most widely used model, but more genetic counselors are reporting variations of this (Cohen et al, ). For example, with the use of genetic counselor extenders, genetic counseling assistants, and development and implementation of programs using educational tools and technology, genetic counselors are improving efficiency and their ability to reach more families (Albada, van Dulmen, Spreeuwenberg, & Ausems, ; Cohen & Nixon, ; Pirzadeh‐Miller, Robinson, Read, & Ross, ; Wang et al, ; Williams et al, ). Collaboration with other healthcare providers and the provision of genetic counseling using video conferencing with patients (telegenetics) and telephone genetic counseling are addressing geographical barriers (Figure ).…”
Section: Service Delivery Innovationmentioning
confidence: 99%
“…Alternatively, for less complex cases, the PCP may feel confident to provide the genetic services directly, especially if they have access to a genetic counselor via supportive education, a consultative service or test utilization management service. Finally, a genetic counselor extender, collaborating with a certified genetic counselor, may allow triage for lower complexity cases (Cohen & Nixon, ). As primary care practices are integrated with larger healthcare systems, the logistics of developing a multimodal and collaborative approach to access genetic counseling services may be feasible as the cost of developing the service is spread across all the specialties that benefit from utilization of genetic testing and counseling.…”
Section: Future Directions: Challenges and Opportunitiesmentioning
confidence: 99%